Evaluation of the Use of CD-ROM Upload into the PACS or Institutional Web Server - van Ooijen, P. M. A. (Springer-Verlag, 2006)
PURPOSE: Patient data are increasingly distributed between hospitals using CD-ROMs instead of actual films. This introduces problems because different viewers from different vendors are provided, and sometimes viewers are unusable because local software installation is not allowed. In 2004, we started to facilitate the incorporation of CD-ROM data into the normal workflow of the hospital by using commercially available software to perform patient reconciliation based on the DICOM (digital imaging and communication in medicine) modality worklist. The purpose of the current study is to evaluate this new procedure. METHODS AND MATERIALS: A questionnaire was sent to all users to evaluate the satisfaction with the current facility and to evaluate possible improvements. Several quality parameters on speed and satisfaction were rated on a 5-point scale (1 = bad to 5 = excellent). RESULTS: Replies from 17 different respondents were evaluated, accounting for an average of 76 CD-ROMs per week. Mean (median) results showed a score of 3.6 (4) for handling time, 3.4 (4) for archival of second opinion data, 3.8 (median 4) for archival of external data onto the web server, and 4.5 (median 5) for the overall performance of the current procedure. CONCLUSION: Although some improvements can be made, storage of the study data from CDs from outpatients into PACS (picture archiving and communication system) and web server already provides for an existing need. Using this service, physicians can access the data with ease and familiarity. User satisfaction with the provided solution is high.